Implementation of Integrated Digital Onboarding Strategy in the Ministry of Transportation for Organizational Alignment and Adaptation - Kurniawanto, Hari (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: The digital transformation in human resource management has led organizations to adopt digital onboarding as a strategy to accelerate new employee adaptation and enhance alignment with organizational values. This study aims to analyze the impact of digital onboarding on organizational value alignment and adaptation speed while examining the mediating role of organizational value alignment in this relationship.Methodology: This study employs Partial Least Squares - Structural Equation Modeling (PLS-SEM) to analyze data collected from new employees at the Ministry of Transportation.Finding: The results indicate that digital onboarding significantly influences organizational value alignment (β = 0.67, p < 0.001) and employee adaptation speed (β = 0.59, p < 0.001). Additionally, organizational value alignment mediates the relationship between digital onboarding and adaptation speed (β = 0.32, p < 0.001), emphasizing the importance of value internalization in the adaptation process.Conclusion: These findings confirm that effective digital onboarding enhances new employee integration and understanding of organizational values. Organizations should design more interactive and experience-based digital onboarding programs to maximize their impact on employee adaptation.